The outer influence inside us: exploring the relation between social and personal norms - Bertoldo, R. (2017)
International efforts for a more sustainable society have often resorted to formal agreements. But these commitments are more effective if people, communities and institutions integrate them as relevant behavioural standards, or social norms. In this paper we propose to analyse how social norms are internalized as personal norms and environmental identity, and then how able they are to predict recycling and organic foods purchase behaviour in two countries—Portugal and Brazil. The role of group identification is also analysed. Results show that behaviours are better predicted by personal norms and environmental identity than by more external social norms. Moreover, the influence of social norms on personal norms and environmental identity is in part moderated by group identification: Injunctive norms predict personal norms and environmental identity better when participants are more identified with the group, while descriptive norms predict them more directly.